Slope Stability Analysis Along The Selected Road Section From Morka-Gircha-Chencha Road, Gamo Zone, Southern Ethiopia - Hayat Abdela (ASTU, 2024)
Slope failures are among the most common geo-environmental natural hazards in the world's steep and mountainous terrain, causing human life to be lost and civil engineering infrastructure to be destroyed. In southern Ethiopia, the road connecting Morka, Gircha, and Chencha traverses through highly harsh terrain with steep hill sides and deep valleys. The current study was carried out to identify and assess the slope stability along chosen road sections, as well as to suggest some remedial solutions based on field investigation and analysis results. A discontinuity survey, in situ rock testing, soil and rock sampling for laboratory analysis, slope geometry, and orientation measurements are all part of the extensive field survey research for this project.The field manifestations also revealed that four key rock slope sections, as well as two essential soil slope sections, were identified for stability research. Planar types of rock slope failure were observed during kinematic analyses using the Dips software at slope sections RSS2 and RSS4. Furthermore, deterministic approaches are employed to calculate the factor of safety by employing Rocplane and planar failures. The stability analysis was performed utilizing limit equilibrium and finite element methods for static dry, static saturated, dynamic dry, and dynamic saturated loading situations. According to the analysis of selected critical slope portions, the slope is stable for FOS larger than one and unstable for FOS less than one. Furthermore, soil laboratory examination found that soils are classed as silty soil and clayey silt (high plasticity), with a liquid limit range of 55.3 to 49.3%, a plasticity index range of 24.3 to 17.2%, and a moisture content range of 35.5 to 30.83%. The finite element results show that crucial soil slope sections three are unstable in static dry and dynamic dry conditions, but it is unstable in static saturated and dynamic saturated situations, and soil six is unstable in all condition. Changes in slope angle, slope height, result in increased slope stability, according to performance study of geometric profiles. Furthermore, the research suggests the placement of rock bolts, anchors, retaining walls, and drainage controls to avoid crucial slope portions from failing.
Keywords: Slope stability analysis, Factor of safety, Kinematic analyze Limit Equilibrium and Finite element method